The Use of Green Tea Extract (Camellia sinensis) Orally to Prevent Dyslipidemia in Female Rats (Rattus norvegicus) Fed A High-Fat Diet - Christina J. R. Esmaralda Lumbantobing; Risna Damayanti; Liena (Jurnal Penelitian Pendidikan IPA, 2023)
One of the significant danger factors for cardiovascular disease and stroke is dyslipidemia. According to long-term prospective epidemiological research, coronary heart disease is less common in those with good lipid profiles who lead better lives. In this study, on a high-fat diet, female wistar rats (Rattus norvegicus) will be tested and analyzed to see if green tea extract (Camellia sinensis) can prevent dyslipidemia when given orally. Compared to a control group that received only distilled water, the trial group that received 5 milliliters of green tea extract (Camellia sinensis) had significantly lower total and LDL cholesterol levels and higher HDL cholesterol levels. This treatment was more effective in lowering cholesterol overall. The components found in green tea (Camellia sinensis), including tannins, steroids, alkaloids, saponins, and flavonoids, can induce this. When certain bioactive substances are off, the body can bring them back into normalcy. These results suggest that white wistar rats (Rattus norvegicus), given a high-fat diet, can benefit from green tea (Camellia sinensis) extract to avoid dyslipidemia. Your lipid profile can be improved by ingesting green tea extract. The primary polyphenol in tea, catechin, is responsible for this transformation. Therefore, the Camellia sinensis plant, from which green tea is made, is a valuable plant that can halt or slow the progression of several ailments, including hypertension, metabolic disorders, and cardiovascular disorders.